O sagrado nas artes: história, acervo e público do Museu de Arte Sacra Escritor Maximiano Campos - Castro, Eva Caroline de Sena (2023)
Museums are spaces dedicated to the conservation and preservation of heritage, whether cultural or artistic, where the public has the opportunity to reflect socially through contact with diverse and plural heritage. The public, on the other hand, is also diverse and heterogeneous, and is a field of research and interest for museums. Thus, the present investigation aims to analyze the experience, in relation to Sacred Art, of the visiting public of the Museu de Arte Sacra Escritor Maximiano Campos (Museum of Sacred Art Writer Maximiano Campos), located in the municipality of Goiana in Pernambuco, Brazil. The research, characterized as a public study, is bibliographical, exploratory, descriptive and documental, under a qualiquantitative approach, shaped as a case study. The research subjects are the students of the courses offered by the Sesc-Goiana culture sector, to which the museum is linked. It uses, as a data collection instrument, a questionnaire composed of open and closed questions. As a data analysis procedure, it uses Content Analysis by establishing thematic categories: socioeconomic profile of the public of the Museu de Arte Sacra Escritor Maximiano Campos; museum attendance and knowledge; motivations, contributions and perceptions of the visit; and particular considerations. The results show that the investigated public shows interest in the museum's exhibitions, that it visits the museum two or more times a year, that it emphasizes the need for greater dissemination of the museum's actions and that their visiting experiences depart from their individual repertoire, aligned with community experiences, since memory permeates the individual and collective fields. It concludes that the historical trajectory, built by the collection of the Museu de Arte Sacra Escritor Maximiano Campos and presented by this museum permeates the history and memory of the municipality of Goiana and its inhabitants, enabling experiences with sacred art, understanding it not only as the symbology and the materialization of the sacred, but also from the perspective of its patrimonial value.